Tentacula, a baroque new genus of jumping spiders from the Brazilian Caatinga (Araneae: Salticidae: Freyina) - Michelotto, Alexandre S.; Santos, Adalberto J. (Zootaxa, 2026)
A new genus is proposed to include its type species Tentacula nordestina gen. et sp. nov., from the Brazilian Caatinga Dominion. This freyine jumping spider is distinguished by a baroque-ornamented, tentacle-like ventral branch of the retrolateral tibial apophysis, a thin, recurved, tapering dorsal tibial apophysis on the male palps, and, in females, by the position of the accessory pockets. This species is described based on males and females with detailed illustrations, and a distribution map is provided. We also discuss its potential affinities within Freyina, copulatory mechanics and ecological associations with moist microhabitats in an otherwise semi-arid region.